2005
DOI: 10.1002/dvdy.20656
|View full text |Cite
|
Sign up to set email alerts
|

Erk1/2 signaling is required for Tgf‐β2–induced suture closure

Abstract: Transforming growth factors ␤ (Tgf-␤s) act by means of Smad signaling pathways and may also interact with the mitogen-activated protein kinase pathway. The hypothesis was tested that Erk1/2 signaling is required for Tgf-␤2-induced suture closure, by culturing embryonic mouse calvariae in the presence of Tgf-␤2 with or without Erk1/2 inhibitor PD98059 (PD). Suture widths were measured daily, and microdissected sutures and bones were homogenized and protein analyzed by Western blots. Tgf-␤2 induced narrowing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
(54 reference statements)
0
24
0
1
Order By: Relevance
“…TGF-b1 and TGF-b2 are expressed in sutures undergoing fusion, whereas TGF-b3 expression is restricted to patent sutures, possibly suggesting that TGF-b1 and TGF-b2 promote, whereas TGF-b3 prevents, closure (Opperman et al 1997;Most et al 1998;Chong et al 2003). In accordance with these observations, TGF-b2 has been shown to induce suture closure in an Erk1 and Erk2 MAPK-dependent manner in an ex vivo murine calvaria model (Opperman et al 2006). In addition to their role in calvaria fusion, BMP and TGF-b signaling are also essential for development and fusion of the palatal shelves (Bush and Jiang 2012).…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 54%
“…TGF-b1 and TGF-b2 are expressed in sutures undergoing fusion, whereas TGF-b3 expression is restricted to patent sutures, possibly suggesting that TGF-b1 and TGF-b2 promote, whereas TGF-b3 prevents, closure (Opperman et al 1997;Most et al 1998;Chong et al 2003). In accordance with these observations, TGF-b2 has been shown to induce suture closure in an Erk1 and Erk2 MAPK-dependent manner in an ex vivo murine calvaria model (Opperman et al 2006). In addition to their role in calvaria fusion, BMP and TGF-b signaling are also essential for development and fusion of the palatal shelves (Bush and Jiang 2012).…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 54%
“…Thus, the unclustered protein acts as a competitive inhibitor of Eph signaling. We tested the ability of clustered ephrin-B2/Fc to stimulate bone growth in ex vivo cultured embryonic mouse calvariae (Opperman et al, 2006). After 5 days of culture, ephrin-B2 treated skulls had double the bone volume of those treated with IgG-Fc control protein ( Fig.…”
Section: Ephrin-b2 Stimulates Bone Growthmentioning
confidence: 99%
“…Calvariae (containing the frontal, parietal, and part of the occipital bones) were harvested from day-17.5 CD-1 mouse embryos and cultured as previously described (Opperman et al, 2006), except that the tissues were cultured for 5 days in alpha-MEM with 10% fetal bovine serum. The medium was changed on day 3.…”
Section: Calvarial Organ Culturementioning
confidence: 99%
“…33 The TGFb2 molecule seems to promote suture fusion, whereas TGFb3 promotes patency. 31 Capitalizing on the therapeutic potential of TGFb, this group demonstrated that application of antibodies to TGFb2 prevented normal molecular signaling and resulted in suture patency. 30,32 Other studies have revealed that treatment of suturectomy sites in rabbits with anti-TGFb2 antibodies can maintain suture patency.…”
mentioning
confidence: 99%